Integrated Individual Learning (PIT) for Digital Literacy and Read-Writing: Pembelajaran Terpadu Berbasis Individu (PIT) untuk Literasi Digital dan Membaca-Menulis - Azhari, Rr. Debby Amalia; Nurdyansyah (Indonesian Journal of Education Methods Development, 2025)
Background: Low digital literacy and read-writing ability among upper elementary students at SDN Penanggungan Trawas limit learning progression. Specific Background: Conventional teaching and limited ICT access reduce student engagement in digital literacies. Knowledge Gap: Evidence on the use of Integrated Individual Learning (PIT) to concurrently improve digital literacy and read-writing in this local elementary context is limited. Aim: This study examined whether PIT increases students' digital literacy and read-writing skills. Methods: A descriptive quantitative design with observation, documentation, and questionnaires; purposive sampling of nine upper-grade students; analysis with paired t-tests. Results: Mean digital literacy rose from 46.25 to 75.70; read-writing mean increased from 63.31 to 77.64; overall mean increased from 54.78 to 76.67, with statistically significant paired differences (p < 0.001). Novelty: The study demonstrates PIT as a combined individual and digital approach adapted to resource-limited elementary settings. Implications: PIT may serve as a practical option for teachers to strengthen both digital and foundational literacy skills in small-group or remedial contexts.Highlights:• PIT raised digital literacy mean from 46.25 to 75.70• Read-writing mean improved from 63.31 to 77.64• Positive student receptivity to digital-based individual learning Keywords: Integrated Individual Learning, Digital Literacy, Read-Writing, Elementary Education, PIT